Assessment Of Risk Priority Number Of 2.5 Mw Polycrystalline Silicon Photovoltaic Power Plant At Navrongo, Ghana In Sub-Sahara Africa. - ALHASSAN SULLAIMAN (KNUST, 2024)
A Thesis Submitted to the Department of Mechanical Engineering, Kwame Nkrumah University of Science and Technology, Kumasi in partial fulfilment of the requirement for the award degree of MASTER OF PHILOSOPHY IN MECHANICAL ENGINEERING